Exploring YouTube users' reactions to bullying incidents / Hanis Diyana Kamarudin, Ekjyot Kaur and Aniza Jamaluddin - Kamarudin, Hanis Diyana; Kaur, Ekjyot; Jamaluddin, Aniza (Faculty of Information Management, 2023)
This research paper explores into the responses of YouTube viewers who encounter videos depicting heinous acts of bullying among teenagers. For this case study, the researchers selected three YouTube videos featuring instances of adolescent bullying were selected. The content of these video clips, along with the reactions and comments of viewers, was analyzed and categorized. The findings of this study shed light on the complex spectrum of viewer responses. The statistical analysis revealed that most viewers expressed profound displeasure and condemnation of the featured video clips, reflecting a widespread societal concern for the victims. Conversely, a minority of viewers appeared to endorse or encourage such behaviour, underscoring the complexity of public attitudes on the platform. This research contributes to our understanding of the multifaceted role of social media as a medium for information dissemination while highlighting its unintended role in facilitating and perpetuating harmful behaviours that demand monitoring and intervention. The study also highlights the apprehension that bullying incidents may become more prevalent, particularly among teenagers, necessitating more proactive measures to address this growing issue. In a world where social media platforms are integral to communication and interaction, comprehending their influence on societal challenges like bullying is crucial. The findings of this research provide valuable insights into the dynamics of online reactions to bullying incidents, offering a foundation for developing strategies and interventions to combat this evolving threat to the well-being of young individuals in the digital age.